Removal of As Using Chitosan–Montmorillonite Composite: Sorptive Equilibrium and Kinetics - Ansar Anjum; Chand K. Seth; Monika Datta (Adsorption Science & Technology)
In this study, the sorptive removal of As 3+ with promising sorption efficiency up to a very low concentration has been investigated using chitosan–montmorillonite (MMT) composites (in the form of powder and beads). In addition, the recovery of the composite from the sorbent is proposed as well. The sorbent has been observed to show a sorption efficiency of 42.0% from 0.006 μg ml −1 of metal ion. The batch adsorption model was developed to predict the equilibrium adsorption capacity with respect to the pH of As 3+ solution, contact time and initial concentration of metal ion. The maximum As 3+ sorption capacity of 48.7 mg g −1 (achieved within 10 minutes of contact time) was obtained using chitosan–MMT beads at the pH of drinking water (8.0) at 298 K. The equilibrium sorption data were fitted to the Langmuir and Freundlich adsorption models and the model parameters were evaluated, wherein the Freundlich model shows the most favourable representation of As 3+ adsorption behaviour. The biocomposites show comparable high sorption capacity with detection and estimation of As 3+ from 0.004 (4.0 ppb) to 100.00 μg ml −1 (100.0 ppm) of aqueous solution. The adsorption kinetics demonstrated intra-particle diffusion as the rate-determining step during the initial phase of adsorption (up to 10 minutes of contact time), which were supported by X-ray diffraction studies; by contrast, chemisorption was found to be the rate-determining step during the later part of adsorption (after 10 minutes of contact time), which were confirmed by Fourier transform infrared spectroscopy-attenuated total reflectance studies. Desorption of As 3+ from the sorbents was optimized using potassium dihydrogen phosphate, wherein 0.1 M of the desorbate was found to be an appreciable regenerating agent supporting the reusability of the sorbent up to three cycles, retaining 4402 μg g −1 of the metal ion.